2002
DOI: 10.1021/jp021217d
|View full text |Cite
|
Sign up to set email alerts
|

Study by Small-Angle Neutron Scattering of Sodium Dodecyl Sulfate Micelles with the Macrocyclic Ligand [2.2.2]Cryptand

Abstract: The addition of [2.2.2]cryptand (C222) to sodium dodecyl sulfate (SDS) micelles in aqueous solution is studied by small-angle neutron scattering (SANS). Hydrogenated and perdeuterated SDS micelles with 8% (wt/wt) concentration have been studied in the presence of 0.5, 1.0, and 1.5 mole ratio C222/surfactant. SANS analysis was performed using a two-shell model for the micelle form factor (core plus interfacial layer) and a screened Coulomb interactive potential for the interparticles potential. For both deutera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…This investigation revealed that, in spite of the good solubility of the cryptand in water, C222 molecule is partitioned at micellar surface and penetrates below the polar head group region [14]. Interestingly, C222 molecule is able to decrease the effective micellar charge and the average aggregation number, as well as to increase the shell thickness.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…This investigation revealed that, in spite of the good solubility of the cryptand in water, C222 molecule is partitioned at micellar surface and penetrates below the polar head group region [14]. Interestingly, C222 molecule is able to decrease the effective micellar charge and the average aggregation number, as well as to increase the shell thickness.…”
Section: Introductionmentioning
confidence: 90%
“…According to small-angle neutron scattering [SANS] measurements [14,21], both ligands solubilize at the micellar surface with the effect of increasing the thickness of the polar head region at the micelle interface, accompanied by a decrease of both the micellar surface charge and the micellar aggregation number.…”
Section: Sds Micellar Solutions In the Presence Of Macrocyclic Ligandsmentioning
confidence: 99%
See 3 more Smart Citations